Multimodal vibration damping using a simplified current blocking shunt circuit. (August 2020) - Raze, Ghislain; Paknejad, Ahmad; Zhao, Guoying; Collette, Christophe; Kerschen, Gaetan
The tuning of a simplified current blocking shunt circuit able to mitigate the vibration amplitude of multiple structural resonances is addressed in this article. The proposed strategy exploits the two-port network formalism in combination with physically motivated approximations to tune sequentially the electrical elements of the different branches of the shunt circuit. The resulting tuning method does not resort to optimization algorithms and requires only the knowledge of quantities that are easy to measure experimentally. It is demonstrated both numerically and experimentally using a piezoelectric beam.